2018
DOI: 10.4103/psychiatry.indianjpsychiatry_300_17
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting quality of life of caregivers of children diagnosed with autism spectrum disorder

Abstract: Context:Since autism spectrum disorder (ASD) is a lifelong disease and because of its nature, the negative effects of the disease on the quality of life (QoL) of caregivers as well as patients are incontrovertible.Aims:It was aimed to evaluate the effect of the variables related to both parents and children on the QoL scores of the parents of the children with ASD.Settings and Design:This is a causality analysis study.Subjects and Methods:Questionnaire on sociodemographic/disease-related variables, QoL in Auti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…Between 69 and 79% of individuals with ASD experience at least one additional psychiatric condition during their lifetime (Buck et al 2014 ; Lever and Geurts 2016 ). Furthermore, ASD and co-occurring conditions can impose a significant emotional burden and negatively affect the quality of life (QoL) of both patients and their families (Chiang and Wineman 2014 ; Özgür et al 2018 ; Picardi et al 2018 ).…”
mentioning
confidence: 99%
“…Between 69 and 79% of individuals with ASD experience at least one additional psychiatric condition during their lifetime (Buck et al 2014 ; Lever and Geurts 2016 ). Furthermore, ASD and co-occurring conditions can impose a significant emotional burden and negatively affect the quality of life (QoL) of both patients and their families (Chiang and Wineman 2014 ; Özgür et al 2018 ; Picardi et al 2018 ).…”
mentioning
confidence: 99%
“…[ 31 ] Local surveys confirmed that longer duration of ASD could directly lead to poorer quality of life among carers. [ 32 33 ] Mothers tend to harbour a wide range of negative thoughts related to death and mortality that help shape their depressive cognitions. [ 34 ] The constellation of distress, depressive symptoms, and difficulties coping with ASD children needs, substantially negatively impact parents' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the studies in which mothers exhibited more depressive symptoms and had lower QoL the more time spent with their children compared to the fathers in the sampling group. 18,19 Hence, since mothers are typically displayed as the caregivers of the household, their QoL is often more affected negatively. The lower social relationship scores were due to mothers having less time for leisure activities in their personal relationships since they would often attend to the demands of their children.…”
Section: Demographic Variablesmentioning
confidence: 99%
“…Moreover, a dissatisfied, satisfied, and neither dissatisfied nor satisfied health satisfaction reduced social relationship scores by 24.230 (Odds ratio: -24.230, 95% CI: -42.963 to -5.497), 23.299 (Odds ratio: -23.299, 95% CI: -41.474 to -5.123), and 19.263 (Odds ratio: -19.263, 95% CI: -37.999 to -0.528) points, respectively (Table7). These results suggest that a better social relationship was predicted in parents with an improved QoL and health satisfaction.A very poor, poor, and neither poor nor good QoL reduced environmental score by19.285 (Odds ratio: -19.285, 95% CI: -33.540 to -5.030), 15.054 (Odds ratio: -15.054, 95% CI: -28.081 to -2.027), and 14.182 (Odds ratio:…”
mentioning
confidence: 99%